2008
DOI: 10.1377/hlthaff.27.2.w145
|View full text |Cite
|
Sign up to set email alerts
|

Health Spending Projections Through 2017: The Baby-Boom Generation Is Coming To Medicare

Abstract: ABSTRACT:The outlook for national health spending calls for continued steady growth.Spending growth is projected to be 6.7 percent in 2007, similar to its rate in 2006. Average annual growth over the projection period is expected to be 6.7 percent. Slower growth in private spending toward the end of the period is expected to be offset by stronger growth in public spending. The health share of gross domestic product (GDP) is expected to increase to 16. N at i o na l h e a lt h s p e n di n g is expected to grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(80 citation statements)
references
References 5 publications
1
79
0
Order By: Relevance
“…1,2 Medicare's revenues are mostly derived from earmarked taxes and general government revenues, with smaller funding streams from beneficiary premiums, state payments, taxes on Social Security benefits, and a few other sources. 3 Medicare has two trust funds: the Hospital Insurance Trust Fund (HITF), financed mostly through payroll taxes (and interest on past surpluses), primarily pays for inpatient care.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Medicare's revenues are mostly derived from earmarked taxes and general government revenues, with smaller funding streams from beneficiary premiums, state payments, taxes on Social Security benefits, and a few other sources. 3 Medicare has two trust funds: the Hospital Insurance Trust Fund (HITF), financed mostly through payroll taxes (and interest on past surpluses), primarily pays for inpatient care.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A recent survey by Casalino et al found that physicians spend on average 3 h each week interacting with health plans. 4 This time is spent on several administrative tasks, including confirming whether a prescribed medication is covered by a plan's formulary, determining whether a certain specialist is part of a plan's preferred network, and dealing with preauthorization forms.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to greater expenditures by the government, which now pays nearly half of total health care spending, 1 employers are paying more for health care, often at the expense of workers' wages. 2 These rising costs make obtaining health care more challenging for the underinsured and uninsured and, before the subprime mortgage collapse, health care costs were the leading cause of personal bankruptcy.…”
mentioning
confidence: 99%